New creation in Paul's letters and thought - Hubbard, Moyer V. (Monograph series (Society for New Testament Studies), 2002)
As a biblical motif, 'new creation' resonates throughout the pages of the Jewish and Christian Scriptures, and occupies a central place in the apostle Paul's vision of the Christian life. Yet the biblical and extra-biblical occurrences of this theme vary widely in meaning, referring to either a new cosmos, a new community, or a new individual. Beginning with the Old Testament and working through the important texts of Second Temple Judaism, Moyer V. Hubbard focuses on how the motif functions in the argument, strategy, and literary structure of these documents, highlighting its role as the solution to the perceived plight. He then explores in detail which senses of the term Paul intends in Galatians 6.15 and 2 Corinthians 5.17, concluding that 'new creation' in Paul's letters describes the Spirit-wrought newness of the person in Christ, and is fundamentally anthropological in orientation.